Borders as Crossroads: The Diverging Routes of Herbal Knowledge of Romanians Living on the Romanian and Ukrainian Sides of Bukovina - Giulia Mattalia; Giulia Mattalia; Nataliya Stryamets; Anya Grygorovych; Andrea Pieroni; Andrea Pieroni; Renata Sõukand (Frontiers Media S.A., 2021)
Cross-border and cross-cultural ethnomedicine are novel ways to address the evolution of local ecological knowledge. As is widely acknowledged, ethnomedicinal knowledge is not static, but evolves according to several factors, including changes in ecological availability and socioeconomic conditions, and yet the effect of the political context on medicinal knowledge remains largely underexplored. Bukovina, a small region of Eastern Europe that has been divided by a border since the 1940s and is currently part of both Romania and Ukraine, represents a unique case study in which to address the impact of political contexts on ethnomedicinal knowledge. The aim of this study was to compare plant-based medicinal uses among Romanians living on the two sides of the Romanian-Ukrainian border. In addition, we performed cross-cultural and cross-border analysis with published data on the ethnomedicine of the neighboring ethnolinguistic group of Hutsuls. We conducted 59 semistructured interviews with conveniently selected Romanians living in both Romanian and Ukrainian Bukovina. We elicited preparations for treating different ailments and disorders by naming each part of the body. We also asked about the sources of this medicinal knowledge. We documented the medicinal use of 108 plant taxa belonging to 45 families. Fifty-four taxa were common to both Romanian communities; 20 were only found among Romanians living in Romania and 34 only among Romanians living in Ukraine. However, the number of recorded uses was higher among Romanians living in Romania, revealing that they make consistent use of local medicinal plants, and Romanians living in Ukrainian Bukovina use more taxa but less consistently. Comparison with the data published in our study on neighboring Hutsuls shows that medicinal knowledge is more homogeneous among Hutsuls and Romanians living in Ukraine, yet many similar uses were found among Romanian communities across the border. We argue that the 50 years during which Ukrainian Bukovina was part of the USSR resulted in the integration of standard pan-Soviet elements as evidenced by several plant uses common among the groups living in Ukraine yet not among Hutsuls and Romanians living in Romania.